Gender differences in percutaneous coronary intervention for chronic total occlusions from the ERCTO study. Issue 5 (8th March 2023) - Avran, Alexandre; Zuffi, Andrea; Gobbi, Cecilia; Gasperetti, Alessio; Schiavone, Marco; Werner, Gerald S.; Kambis, Mashayekhi; Boudou, Nicolas; Galassi, Alfredo R.; Sianos, George; Idali, Moussa; Garbo, Roberto; et al.
Abstract: Background: Gender‐specific data addressing percutaneous coronary intervention (PCI) of chronic total occlusion (CTO) in female patients are scarce and based on small sample size studies. Aims: We aimed to analyze gender‐differences regarding in‐hospital clinical outcomes after CTO‐PCI. Methods: Data from 35, 449 patients enrolled in the prospective European Registry of CTOs were analyzed. The primary outcome was the comparison of procedural success rate in the two cohorts (women vs. men), defined as a final residual stenosis less than 20%, with Thrombolysis In Myocardial Infarction grade flow = 3. In‐hospital major adverse cardiac and cerebrovascular events (MACCEs) and procedural complications were deemed secondary outcomes. Results: Women represented 15.2% of the entire study population. They were older and more likely to have hypertension, diabetes, and renal failure, with an overall lower J‐CTO score. Women showed a higher procedural success rate (adjusted OR [aOR] = 1.115, confidence interval [CI]: 1.011–1.230, p  = 0.030). Apart from previous myocardial infarction and surgical revascularization, no other significant gender differences were found among predictors of procedural success. Antegrade approach with true‐to‐true lumen techniques was more commonly used than retrograde approach in females. No gender differences were found regarding in‐hospital MACCEs (0.9% vs. 0.9%, p  = 0.766), although a higher rate of procedural complications was observed in women, such as coronary perforation (3.7% vs. 2.9%, p  < 0.001) and vascular complications (1.0% vs. 0.6%, p  < 0.001). Conclusions: Women are understudied in contemporary CTO‐PCI practice. Female sex is associated with higher procedural success after CTO‐PCI, yet no sex differences were found in terms of in‐hospital MACCEs. Female sex was associated with a higher rate of procedural complications.